Microbial enzymatic activity measurements by fluorogenic substrates: Evidence of inducible enzymes in oligotrophic Mediterranean areas - Caruso G; Caruso R; Maimone G (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2019)
Background: In aquatic environments, organic polymers such as proteins, polysaccharides and organic phosphates are cleaved and up taken by microorganisms through the expression of specific enzymes such as Leucine Aminopeptidase (LAP), beta Glucosidase (GLU) and Alkaline Phosphatase (AP), respectively. Microbial enzymatic activities are a fundamental step in the organic matter utilization and turnover into simple monomers.